Differential protein expression profiling by iTRAQ‐2D‐LC‐MS/MS of rats treated with oxaliplatin. Issue 10 (25th June 2019) - Sun, Xianjun; Lv, Yubao; Wang, Junjun; Cheng, HuiQin; Huang, Jianhua; Du, Yijie; Dong, Jingcheng
Abstract: Clinical application of oxaliplatin, a platinum‐based chemotherapeutic agent, in cancer, especially colorectal cancer, is widely used. However, oxaliplatin‐induced peripheral neurotoxicity (OIPN) has a high incidence, and to date, there have been few detailed studies on pathogenesis and treatment mechanisms. The present study was performed by using a proteomic approach to explore protein expression profiling of rats treated with oxaliplatin by multiplex isobaric tags for relative and absolute quantification labeling and two‐dimensional liquid chromatography‐tandem mass spectrometry. There were 74 proteins that showed different expression in sciatic nerve between control rats and OIPN model rats, with 53 upregulated proteins and 21 downregulated proteins detected in OIPN groups compared with control groups. On the basis of Gene Ontology clustering, these proteins were associated with biological processes (eg, muscle contraction, muscle system process, and skeletal muscle contraction), cellular component (eg, myofibril, contractile fiber, and contractile fiber part) and molecular function (structural constituent of muscle, hydro‐lyase activity, and calcium ion binding). On the basis of Kyoto Encyclopedia of Genes and Genomes pathway database, these proteins were associated with African trypanosomiasis, malaria, nitrogen metabolism, etc. Real‐time polymerase chain reaction, Western blot as well as immunohistochemistry analysis was performed to examine the expression of partially differential protein. In conclusion, our study establishes a protein expression profile of oxaliplatin‐induced rats and mechanisms leading to OIPN development, and will be useful for developing novel diagnostic biomarkers and aiding in the prevention and control of OIPN. Abstract : Our study illustrates protein characteristics of sciatic nerve specimens in L‐OHP‐induced rats and emphasizes the importance of proteomics by using isobaric tags for relative and absolute quantification (iTRAQ)‐coupled two‐dimensional liquid chromatography‐tandem mass spectrometry (2D‐LC‐MS/MS). Seventy‐four specific proteins with significant fold changes were identified between controls and oxaliplatin‐induced peripheral neurotoxicity (OIPN) models, provided basic information much needed for recognizing OIPN and designing of more effective targeted therapies.